Nilai Kemanusiaan dalam Lakon Gojali Suta - YB. Rahno Triyogo (Institut Seni Indonesia Surakarta, 2022)
Gojali Suto is one of the Lakon in wayang kulit purwa that tells the conflict of triangular love between Boma, Hagnyanawati, and Samba. The triangular love conflict ended tragically because it resulted in the death of the three conflicting characters. This study emphasizes analytical descriptive studies. The aim of this research is to describe human values by paying close attention to how they resolve the conflicts. The results of the study indicate that the values of humanity that stems from human dignity can be seen in the way of resolving conflicts faced by the characters in the story. Due to the lack of self-control, human values are discarded which cause the destruction. By looking at the way they respond to and resolve the problems they experience, their moral quality will be seen. There are two conclusions obtained from this study. The first is that a fragile personality can be easily influenced by negative forces that come from outside. Second, that the closest people or the most trusted people can become enemies that are not detected.